1952
DOI: 10.1037/h0059617
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination learning with shock for right and wrong responses in the same subjects.

Abstract: Recently Muenzinger (5) and Wischner (11) have discussed certain differences in the results of their respective experiments on the effect of shock upon the learning of a discrimination habit by the white rat. The present writers do not question the results obtained by either investigator, but call attention to one noteworthy feature: In the studies of both, shock was employed for right choices only, or for wrong choices only. In view of Muenzinger's suggestion (4) that shock anywhere after choice facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1964
1964
1982
1982

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…However, these experiments must be interpreted cautiously with respect to the present analysis. Well over one-third of the response-produced shocks in tone as well as in light were presented simultaneously with food, making it likely that the mild shocks acquired some positive properties through their food-signalling function (see Azrin and Holz, 1966;Freeburne and Taylor, 1952;Logan and Wagner, 1965). [This shock-food correlation is revealed by examination of the training cumulative records presented by Wiltz (1972) when the reinforcement presentations indicated by slash marks of the response pen are lined up with response-produced shocks recorded by the event pen.…”
Section: Two-factor Combinational Model Represented In Response/incenmentioning
confidence: 99%
“…However, these experiments must be interpreted cautiously with respect to the present analysis. Well over one-third of the response-produced shocks in tone as well as in light were presented simultaneously with food, making it likely that the mild shocks acquired some positive properties through their food-signalling function (see Azrin and Holz, 1966;Freeburne and Taylor, 1952;Logan and Wagner, 1965). [This shock-food correlation is revealed by examination of the training cumulative records presented by Wiltz (1972) when the reinforcement presentations indicated by slash marks of the response pen are lined up with response-produced shocks recorded by the event pen.…”
Section: Two-factor Combinational Model Represented In Response/incenmentioning
confidence: 99%
“…The initial finding (Muenzinger, 1934), that a shock which was twice the threshold value for young rats (Muenzinger & Mize, 1933) would actually facilitate the learning of a light-dark discrimination beyond the influence of reward alone, was confirmed in a number of subsequent investigations (Muenzinger & Baxter, 1957;Muenzinger, Bernstone, & Richards, 1938;Muenzinger, Brown, Crow, & Powloski, 1952;Muenzinger & Powlowski, 1951;Muenzinger & Wood, 1935). Likewise, Drew (1938) and Freeburne and Taylor (1952) found that shock enhanced discrimination learning in rats beyond the effects of reward alone. Rosenblum and Harlow (1963) report a similar effect in connection with a different species operating in a different procedure.…”
Section: Punishmentmentioning
confidence: 90%
“…In proposing their distinctive-cue hypothesis, Fowler and Wischner (1969) stressed difficulty of discrimination as a crucial variable; i.e., shockright facilitation increased with difficulty. It is worth noting that Freeburne and Taylor (1952), who found indiscriminate shock facilitating, used a 5-sec. delay of reward and that 6 of their 20 -?s failed to solve the problem in 500 trials.…”
Section: Discussionmentioning
confidence: 99%
“…The most decisive test of Muenzinger's (1934) theory is to compare a nonshocked SEWARD, ROSKIN, KOSSLYN, GREATHOUSE, AND WEXLER group with one shocked after all responses, correct or incorrect. This test has been made four times before, twice with positive results (Freeburne & Taylor, 1952;Muenzinger & Wood, 1935) and twice with negative (Fowler & Wischner, 1969;Prince, 1956). Muenzinger and Wood used the correction method; the other three experiments used noncorrection.…”
Section: Experiments Imentioning
confidence: 99%
See 1 more Smart Citation